Organised governmental learning : vocational education and training practices between peer review and peer learning - Speer, Sandra [Verfasser] (My University, 2011)
"Peer learning has already existed for a long time, as an informal as well as a formal practice between people from the same professional area. However, peer learning systems on the macro level are relatively newer concepts. Policy learning can be fostered by various types of organised activities, ranging from peer review frameworks, which often have a focus on accountability and learning, to international learning events, which are based on concepts like the 'learning spiral'. This article reviews existing international practices of organised governmental learning on the system level, which are also linked to processes on the micro level. It thereby gives a framework to discuss two different VET peer learning activities across Europe which are organised by the European Union (EU) and the European Training Foundation (ETF)." (Authors' abstract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 5.2 Wissensmanagement; I 2.2 Europa; Berufsbildungspolitik; Bildungsreform; Lernende Organisation; Wissenstransfer; Peer Review; Europa